2010
DOI: 10.1177/1073858410379268
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Bases for Empathy

Abstract: Human empathy relies on the ability to share emotions as well as the ability to understand the other's thoughts, desires, and feelings. Recent evidence points to 2 separate systems for empathy: an emotional system that supports our ability to empathize emotionally and a cognitive system that involves cognitive understanding of the other's perspective. Converging evidence from neuroimaging and lesion studies shows that a neural network that includes the inferior frontal gyrus and the inferior parietal lobule is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
601
1
21

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 888 publications
(651 citation statements)
references
References 36 publications
28
601
1
21
Order By: Relevance
“…These findings indicate that OT may selectively attenuate reactivity in limbic structures involved in stress and anxiety (amygdala), while simultaneously enhancing activity of dopaminergic motivational circuits that underlie reward learning and parenting behaviors (VTA). In addition, OT may contribute to enhanced emotion recognition of salient infant social cues through increased activation of specific brain regions (insula and inferior frontal gyrus) that are part of the empathy related brain network (Shamay-Tsoory, 2011). It should be acknowledged, however, that imaging studies using intranasal OT challenge are controversial (Leng and Ludwig, 2015).…”
Section: Ot and Early-life Stress (Els) – Role In Shaping Neural Cmentioning
confidence: 99%
“…These findings indicate that OT may selectively attenuate reactivity in limbic structures involved in stress and anxiety (amygdala), while simultaneously enhancing activity of dopaminergic motivational circuits that underlie reward learning and parenting behaviors (VTA). In addition, OT may contribute to enhanced emotion recognition of salient infant social cues through increased activation of specific brain regions (insula and inferior frontal gyrus) that are part of the empathy related brain network (Shamay-Tsoory, 2011). It should be acknowledged, however, that imaging studies using intranasal OT challenge are controversial (Leng and Ludwig, 2015).…”
Section: Ot and Early-life Stress (Els) – Role In Shaping Neural Cmentioning
confidence: 99%
“…This ability is also referred to as mentalizing, mental state attribution, or cognitive empathy [51]. Research in this field has used tasks like: Adult Faux Pas [52], Brune Picture Sequencing Task [53], Happe's Stories [54], Reading the Mind in the Eyes further study.…”
Section: Measuring Social Cognition In Schizophreniamentioning
confidence: 99%
“…Empathy refers to sharing, understanding and responding to the emotional experiences of another person, depending on multiple components of social cognition and is viewed as an example of integration among social processing systems [51,73]. Both experience sharing and mentalizing are included in most models of empathy [24,51], and some models also emphasize the role of emotion regulation as a way to modulate an empathic response when it becomes maladaptive [74]. It was shown that patients with schizophrenia have impairments in monitoring the emotions of others, suggesting that they do exhibit problems in complex social-cognitive abilities such as empathy [75,76].…”
Section: Empathy Impairment In Schizophrenia-an Integrated Model Of Smentioning
confidence: 99%
“…Empathy, a basic prosocial behavior, reflects the natural ability to feel, understand, and share the emotional states of others and is generally divided into emotional (affective) empathy and cognitive empathy [54][55][56][57][58]. Experimental human and animal studies have demonstrated that observing intimates in pain (cagemates for animals) heightens an individual's pain perception, referred to as empathy for pain [15,54,[59][60][61][62][63].…”
Section: Does Mpfc Mediate Ethanol-induced Emotional Empathy?mentioning
confidence: 99%